Business Cycle, Banking Risk-Taking, and Technological Change: European Evidence - BOUHENI, FATEN BEN; SIDAOUI, MOUWAFAC; THEOL, MARGAUX; BELLALAH, MONDHER (Bankers, Markets & Investors, 2025)
This paper explores the risk-taking behavior of European banks over the course of the business cycle with a particular emphasis on systemically important banks (SIBs). The findings suggest that while commercial banks’ liquidity and credit risks tend to be procyclical—rising during periods of economic growth—SIBs exhibit a countercyclical pattern by showing reduced liquidity and credit risks during such times. Often labeled as “too big to fail,” SIBs benefit from financial guarantees and deposit insurance systems that promote the diversification of their activities. Moreover, these banks are equipped with comprehensive risk management strategies. Additionally, economic freedom plays a vital role in reducing the volatility of returns on both assets and equity for SIBs. This stabilization is influenced by market expectations regarding the efficacy of economic freedom for these large financial institutions. The findings underscore the importance of factors such as bank size, economic freedom, financial market structure, and risk-taking culture in sustaining financial stability amid economic uncertainty. Furthermore, banks are increasingly embracing technological advancements, and the integration of fintech continues to present both opportunities and challenges.